In the sphere of silence - Eswaran, Vijay; RYTHM House Publishing ([Singapore] : RYTHM House Publishing, 2007)
The Sphere of Silence (SoS) is a way out, a respite from the noise outside ourselves and inside us so that we can listen to our souls and its deepest aspirations. It is a way of untangling the complicated knots we put on the ropes of our lives, so that we may become simpler and our crooked lives made perfect.
Title from container
Keywords: Silence (Philosophy).; Silence